ATMOSPHERE HEMISPHERIC ANALYSIS OF PARTICLES POLLUTION OVER AFRICA (FUDMA JOURNAL OF SCIENCES, 2023)
Particulate Matters (PM) or particle pollution are mixture of microscopic solid and liquid particles present in air. The presence of PM in air can be monitored through modern devices known as Air Quality Sensors. In this study, we seek to investigate the concentration of PM at different latitude in some regions in Africa using purple air data available at map.purpleair.com  downloaded for a period of 365 days in some African countries namely; Nigeria, Ghana, Ethiopia, Tanzania, Morocco and Zambia. Using Pearson correlational analysis, findings have revealed that the correlation coefficient r between the average PM concentration in some countries within the Northern hemisphere shows -0.91 and 1 for countries lying in the Southern hemisphere. Taken together, these results suggest that there is an association between the PM and latitude. It can therefore be inferred that the higher the country from the northern hemisphere, the lower the concentration of PM and vice versa.
Keywords: Africa; Air quality; Latitude; Particulate Matters; Pollution; Purpleair